TAX PLANNING DETERMINANTS OF CORPORATE TAXPAYERS (A STUDY ON THE CORPORATE TAXPAYERS REGISTERED AT THE SMALL TAX OFFICE OF NORTH MALANG) - Kurniawan, Pandu (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research aims at identifying the tax planning determinants of corporate taxpayers. Tax planning is the first step taken by a taxpayer to minimize the tax payable by obeying the applicable tax regulation; thus, corporate taxpayers are expected to apply the tax planning with regard to the pertinent rules. The primary data of this study are collected through questionnaire given to 65 corporate taxpayers registered at the Small Tax Office (Kantor Pelayanan Pajak Pratama) of North Malang. The samples are taken purposively under judgment sampling type, and the hypothesis is tested by Statistical Product and Service Solutions (SPSS) method. The result of the analysis shows that detection risk, loopholes, taxpayer morality, and tax rate significantly influence the tax planning, with the first factor playing the most influential part. In contrast, tax policy, tax law, and tax administration do not significantly influence the planning. Keywords: Corporate Taxpayer; Tax Planning; Motivation